2015
DOI: 10.1002/jqs.2777
|View full text |Cite
|
Sign up to set email alerts
|

Last deglacial and Holocene lake level variations of Qinghai Lake, north-eastern Qinghai-Tibetan Plateau

Abstract: Qinghai Lake is of significance for paleoclimate research because it lies in a pivotal region that is influenced by both the mid‐latitude Westerlies and the low‐latitude Asian summer monsoon (ASM). Most published lake level histories of Qinghai Lake are interpreted from drill‐core proxies. Here we combine geomorphic shoreline investigations with optically stimulated luminescence dating to constrain lake level variations since the last deglacial. The results indicate that two periods of highstands occurred duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 84 publications
(160 reference statements)
5
64
0
Order By: Relevance
“…However, based on the relatively high %OH‐GDGTs which is less likely influenced by soil input as soil group 1.1b Thaumarchaeota produce crenarchaeol but not OH‐GDGTs, we can confirm that Lake Qinghai was relatively deep during deglaciation, at least intermittently (Figure e). The deglacial intermittent high stand reconstructed by %cren and %OH‐GDGTs is in general agreement with the discontinuous lake‐level record inferred from paleoshoreline deposits (Figure f; Liu et al, ) and is possibly due to high meltwater input or low evaporation loss.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…However, based on the relatively high %OH‐GDGTs which is less likely influenced by soil input as soil group 1.1b Thaumarchaeota produce crenarchaeol but not OH‐GDGTs, we can confirm that Lake Qinghai was relatively deep during deglaciation, at least intermittently (Figure e). The deglacial intermittent high stand reconstructed by %cren and %OH‐GDGTs is in general agreement with the discontinuous lake‐level record inferred from paleoshoreline deposits (Figure f; Liu et al, ) and is possibly due to high meltwater input or low evaporation loss.…”
Section: Resultssupporting
confidence: 85%
“…Comparing past variations in %cren and %OH‐GDGTs with reconstructed paleohydrological history of Lake Qinghai since the last deglaciation. (a) δ 18 O of ostracod shells, used as a proxy for effective precipitation (Liu et al, ); (b) δ 13 C of total organic carbon, with more negative values indicating higher lake level (Liu, Li, et al, ); (c) Water level variations based on ostracod Sr/Ca‐inferred salinity changes (Zhang et al, ); (d) Sketched lake‐level history based on multievidence (Yu, ); (e) %cren (sky blue line; Wang et al, ) and %OH‐GDGTs (orange; 0‐ to 8‐ka data from Wang, Liu, et al ()); (f) Sketched shoreline history for Lake Qinghai, with shoreline elevations plotted against age estimates (Liu et al, ); (g) Thaumarchaeol amoA gene abundance (Yang et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the largest inland lake in China, the variation in the water level of Qinghai Lake has attracted a great deal of attention [30,31]. In our study, the lake water level was shown to have declined from 1959 to 2000, which was consistent with Li [32], who came to the same conclusion that the lake water level had tended to decrease in the years from 1959 to 2000.…”
Section: Discussionsupporting
confidence: 86%
“…During the Late Glacial period, PANN was particularly variable between ~18,000 and ~15,000 cal years B.P., yet consistent with a high lake water‐level reconstructed from paleoshorelines for our study area [e.g., X. J. Liu et al , ; Chen et al , ] and a high annual rainfall amount inferred from 10 Be records for the nearby Chinese Loess Plateau (CLP) [ Zhou et al , ], with westerlies commonly suggested as the dominant driver of paleoclimatic change at this time interval in western and northern China [e.g., An et al , ; Komatsu and Tsukamoto , ; Thomas et al , ]. The plausible explanation might be related to enhanced moisture contents carried by westerlies during the late Pleistocene period with expanded areas of Caspian and Black Seas and increased amounts of melting ice sheets, glaciers, and permafrost in the Eurasian continent, due largely to rapid intensification of total summertime solar insolation in the middle‐ and high‐latitude regions of the Northern Hemisphere [e.g., Clark and Mccabe , ; Badertscher et al , ; Dortch et al , ; X. J. Liu et al , ] (Figure ). The period from ~15,000 to ~13,000 cal years B.P.…”
Section: Resultsmentioning
confidence: 99%